The Role of Vitamin C in Management of Hypertension: A systematic review - Rivani Sintia Suratman; Harnavi Harun; Drajad Priyono; Deka Viotra (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2025)
Background: Vitamin C is an antioxidant that can reduce oxidative stress. Oxidative stress has been thought to play an important role in the pathophysiology of hypertension. Studies have looked at Vitamin C as a supplement to treat hypertension. Vitamin C’s use as a complementary treatment for hypertension remains controversial, nevertheless. This study aims to evaluate vitamin C’s contribution to the treatment of hypertension. Objective: To conduct a literature review that examines how vitamin C (VC) supplements affect hypertension. Methods: This research uses a systematic literature review (SLR) approach with sources obtained from various online databases, including PubMed, Cochrane Library, EBSCO, and Elsevier, using the keywords